Ketaatan Masyarakat Islam Pedesaan Dalam Menjaga Lingkungan Dari Sampah - M. Amir Mahmud; Iis Jannah (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The indiscriminate disposal of waste in villages, particularly in Banyuwangi Regency, has become a crucial phenomenon. In addition to the increasing daily waste, the lack of sanitation facilities and the low literacy of the community regarding waste raise concerns. The impacts involve unpleasant odors, environmental pollution, unsightly views, and the potential spread of diseases. Numerous illegal dumping points along riverbanks pose a threat to rice field irrigation. Previous studies primarily focused on factors such as attitudes and education levels, neglecting the anthropological aspects of Islamic law. This research addresses this gap by examining the behavior of rural communities towards waste in Banyuwangi from the perspective of Islamic law anthropology. The study is significant as the indiscriminate disposal of waste persists among rural Islamic communities, despite existing Islamic laws requiring environmental protection. The qualitative research method, specifically explanatory case studies, was conducted in Sarimulyo Village in December 2023. The results indicate a lack of knowledge among the community regarding waste and Islamic law, along with a tendency for non-compliance with regulations.